Analisis Gharar dan Maisir dalam Trading Cryptocurrency: Tela’ah Perspektif Tafsir Kontekstual - Riza Fabian Harahap; Hery Sahputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The rapid development of cryptocurrency as a component of the digital economy has generated significant debate regarding its compatibility with Islamic economic principles, particularly concerning the concepts of gharar (uncertainty) and maisir (speculation/gambling). This study aims to analyze the characteristics of cryptocurrency trading through a contextual Qur’anic exegesis of verses related to economic transactions. Employing a qualitative library research approach, the study draws upon Qur’anic verses, classical and contemporary tafsir literature, as well as scholarly works on cryptocurrency and Islamic economics. Data were analyzed using the thematic (maudhu‘i) interpretation method, focusing on Qur’an Surah Al-Baqarah [2]: 275 and 282, An-Nisa [4]: 29, and Al-Ma’idah [5]: 90. The findings reveal that gharar in the Qur’anic perspective refers to substantial uncertainty and ambiguity that may lead to injustice and loss in transactions, while maisir denotes economic activities dominated by speculation and profit-seeking without a balanced exchange of value. The characteristics of cryptocurrency trading, including extreme price volatility, speculative market behavior, and uncertainty regarding asset valuation, exhibit strong similarities to the elements of gharar and maisir, particularly in short-term trading and cryptocurrency derivative markets. Nevertheless, the study also finds that not all cryptocurrency-related activities can be categorically classified as involving gharar or maisir, as such assessments depend on the transaction mechanism, the degree of transparency, and the intended use of the digital asset. This research demonstrates that Qur’anic values of justice, transparency, and economic balance remain relevant as ethical and normative frameworks for evaluating contemporary digital economic practices and contribute to the development of Qur’anic economic interpretation in the era of financial technology.